Elites, Climate Change and Agency in a Developing Society: The Chilean Case - Letelier-Sotomayor, M; Muñoz-Correa, J; Parker-Gumucio, C (2013)
Faced with global climate change, local elites are confronted with the main dilemma of a developing country: development requires economic growth, but this effort also requires consideration of environmental factors and sustainable patterns of production and consumption. Based on empirical evidence from qualitative research on businesses and political elites in Chile-a paradigmatic South American middle-income country-this paper explores the extent to which local elites are aware of the severity of challenges posed by global climate change and identify main climate change concerns in their discourse. The degree to which domestic elites are aware of the paradigm shift they must assume toward clean industrial production is a key issue of environmental governance that involves private non-governmental actors. This paper gives clues to a better understanding of what is happening with strategic actors in developing nations and their understanding of their decision-making capacity concerning environmental policy and investments for facing global climate change. The main conclusion of the research is that awareness of climate change in local elites discourse is relative. It is not accompanied by a full acceptance of their agency and is not leading to a paradigm shift toward a clean model of development because of domestic elites position within globalization processes. © 2013 Springer Science+Business Media Dordrecht.